Production and evaluation of monoclonal antibody against Strongyloides ratti - Aliyu, Mahmuda (2017)
Currently, most of the available serological diagnostic kits for strongyloidiasis are based on the application of the crude antigens of Strongyloides ratti, which are good, but with less sensitivity for diagnosis of active infection. Hence this study is aimed to produce and evaluate monoclonal antibody for detecting soluble parasite antigen in animal sera prior to hyper infection and disseminated strongyloidiasis. Strongyloides ratti infection model was established and maintained in immunosuppressed Sprague Dawley rats. Saline extract protein from the infective larvae (iL3) of Strongyloides ratti was used to immunise BALB/c mice. The B-lymphocytes from the spleen taken from the immunised mice were fused with myeloma (SP2/0) cells using 50% polyethylene glycol (PEG) for somatic cell hybridization. The hybridomas were cultured in hypoxantine-aminopterin-thymidine (HAT) medium and cloned by limiting dilutions. Supernatants from the growing positive hybrids were screened by indirect ELISA using 96-well plates coated with the saline extract-protein. The ascites fluid induced by intraperitoneal injection of the antibody-secreting hybridoma cells was purified by a MAb IgG purification kit. The purified antibody (MAb) was characterised by western blots and evaluated in capture ELISA for reactivity against the homologous and heterologous antigens of Ascaris suum, Toxocara canis, Ancylostoma caninum and Toxoplasma gondii. An IgG1 MAb that recognises 30 kDa and 34 kDa associated with strongyloidasis and a cross-reaction with a 30 and 34 kDa for toxocariasis were observed. This indicates that more than one epitope is recognised by the MAb, thus, making it valuable for diagnostic purpose. The MAb was recognised by all Strongyloides ratti antigens and Toxocara canis antigens but did not react with other heterologous antigens in both assays. From the results obtained using the saline extract protein antigen concentration standard curve, it is confirmed that the antigen detection limit by sandwich ELISA was 5 ng/mL, which provides sufficient sensitivity for the diagnosis of Strongyloidiasis. All twelve (12) strongyloidiasis infected rat sera evaluated for circulating antigen using the MAb produced, have shown antigen-positive reactions in sandwich ELISA. Similar results were obtained from Toxocara infected animal sera. This study concluded that the MAb produced was able to detect strongyloidiasis and toxocariasis in animal models and may also be used for serological diagnosis of strongyloidiasis and toxocariasis in human sera.